PENGARUH BIMBINGAN BELAJAR DI LUAR SEKOLAH DENGAN MODEL PEMBELAJARAN EXPOSITORI TERHADAP HASIL BELAJAR SISWA KELAS 3 SMA DI BANYUWANGI - Ferdiana, Ferdiana (JEAS (Journal of Educational and Applied Science), 2023)
The main problem faced by Indonesian education is the low quality of education at every level and unit of education. Many factors cause the low quality of education in Indonesia. One of them is the curriculum that has always been centralized, ignoring diversity and only oriented towards mastery of subject matter. Most students have a pattern of learning diligently and painstakingly, but the results obtained are less than optimal and there are types of students who study only approaching exams with unscheduled study time, but get less than optimal results. The solution that can be done is to use the expository learning model, in expository learning the teacher tends to hold the control of the active learning process, while students are relatively passive in accepting and following what is presented by the teacher. Expository learning is a teacher-centered learning, in which the teacher becomes the main source and provider of information with the intention that students can master the learning material optimally. The research method used is quantitative research. The result of the T test Research is 1.684 (> sg 0.05) which states that count> t table means accepting Ho, therefore there is a difference in the effect of the expositosi learning model on learning outcomes in biology subjects that follow out-of-school tutoring for 3rd grade high school students.